Analysis of Needs for the Development of Electronic Teaching Materials Based on Problem-Based Learning (PBL) - Reno Esa Mahendra; Astrid Sri Wahyuni Sumah (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: The learning process emphasizes students' active involvement and is oriented towards applying the concept of learning by doing and prioritizing personal experiences through observing, asking, and communicating to increase student creativity. However, reality proves that the application and implementation of learning in schools are not as expected. Some problems include the learning process only focusing on completing the subject matter, not on forming an understanding of the subject matter for students. This study aimed to analyze the need to develop electronic teaching materials according to the needs of students based on problem-based learning (PBL) learning models in biology subjects at MAN 1 Palembang school. Methods: The research used a qualitative descriptive method with a survey method by conducting interviews and questionnaires with biology teachers and students. Questionnaires, observations, and interviews provided data collection techniques. Results: The results obtained are textbooks and learning videos are the teaching materials most often used by teachers using discovery learning and project-based learning (PjBL) models. Students' activeness can be seen when the discussion activities and presentations of assignments take place, but it does not make students think critically. Conclusion: Teachers want problem-based learning (PBL) electronic teaching materials so that students can learn the material earlier and improve learning outcomes in material that is difficult for students to understand.